Listeriosis in a Metropolitan Hospital: Is Targeted Therapy a Risk Factor for Infection? - Xing, Fanfan; Lo, Simon K. F.; Lau, Susanna K. P.; Woo, Patrick C. Y. (Frontiers in Medicine, 2022)
Targeted therapies are widely used for treatment of autoimmune diseases as well as solid organ and hematological malignancies. Various opportunistic infections have been described in patients on targeted therapies. Although case reports or a few case series of listeriosis have been reported to be associated with targeted therapy, most of the cases were related to anti-tumor necrosis factor-α monoclonal antibody. In this study, we describe the epidemiological and clinical profiles of listeriosis in a tertiary hospital in Shenzhen, a Southern Chinese metropolitan city in China. During the nine-year-and-six-month study period, a total of five cases of listeriosis were recorded and all of them had Listeria monocytogenes bacteremia. All five patients had predisposing factors, including corticosteroid (n=3), targeted therapy (n=2), pregnancy (n=2) and anti-interferon gamma autoantibody (n=1). The two patients who had targeted therapy during their course of cancer treatment received inhibitors of the epidermal growth factor receptor (EGFR)/human epidermal growth factor receptor 2 (HER2) pathway. The first one was a 52-year-old woman with metastatic adenocarcinoma of the lung. She was given gefitinib (EGFR tyrosine kinase inhibitor), osimertinib (third-generation EGFR tyrosine kinase inhibitor) and afatinib (tyrosine kinase inhibitor that can bind to EGFR, HER2 and HER4). The second one was a 40-year-old woman with carcinoma of the breast with brain metastasis. She was given trastuzumab (anti-HER2 monoclonal antibody) and lapatinib (dual tyrosine kinase inhibitor of the EGFR/HER2 pathway). These two patients represent the second and third reports of listeria infections associated with EGFR/HER2 pathway inhibitors in the literature. Targeted therapy is an important predisposing factor for listeriosis. Listeria infection is an important differential diagnosis in patients on targeted therapy who present with sepsis and/or central nervous system infection, and the use of antibiotic regimens that cover listeria is crucial for empirical treatment. Avoidance of high-risk food items in these patients is important for the prevention of listeriosis.